Odpowiedź:
a)
2 - (x + 3)/3 < (2x - 3)/2 | * 6
6 * 2 - 2(x + 3) < 3(2x - 3)
12 - 2x - 6 < 6x - 9
- 2x + 6 < 6x - 9
- 2x - 6x < - 9 - 6
- 8x < - 15
8x > 15
x > 15/8
x > 1 7/8
x ∈ ( 1 7/8 ; + ∞ )
b)
(2 - x)/2 - (2x - 1)/3 ≤ 1 - x \ * 6
3(2 - x) - 2(2x - 1) ≤ 6(1 - x)
6 - 3x - 4x + 2 ≤ 6 - 6x
- 7x + 8 ≤ 6 - 6x
- 7x + 6x ≤ 6 - 8
x ≤ - 2
x ∈ (- ∞ , - 2 >
c)
(x + 4)/12 + 1 ≥ x/6 - (3 - x)/4 | * 12
x + 4 + 12 ≥ 2x - 3(3 - x)
x + 16 ≥ 2x - 9 + 3x
x + 16 ≥ 5x - 9
x - 5x ≥ - 9 - 16
- 4x ≥ - 25
4x ≤ 25
x ≤ 25/4
x ≤ 6 1/4
x ∈ (- ∞ , 6 1/4 >